Characterization of GASA-1, a new vaccine candidate antigen of Babesia bovis - Flores, Daniela (2020)
Surface proteins bound to the cell membrane by glycosylphosphatidylinositol (GPI) anchors are considered essential for the survival of pathogenic protozoans. In the case of the tick-transmitted hemoparasite Babesia bovis, the most virulent causative agent of bovine babesiosis, the GPI-anchored proteome was recently unraveled by an in silico approach. In this work, one of the identified proteins, GASA-1 (GPI-Anchored Surface Antigen-1), was thoroughly characterized. GASA-1 is 179 aa long and has the characteristic features of a GPI-anchored protein, including a signal peptide, a hydrophilic core and a hydrophobic tail that harbors a GPI anchor signal. Transcriptomic analysis shows that it is expressed in pathogenic and attenuated B. bovis strains. Notably, the gasa-1 gene has syntenic counterparts in B. bigemina and B. ovata, which also encode GPI-anchored proteins. This is highly unusual since all piroplasmid GPI-anchored proteins described so far have been found to be species-specific. Sequencing of gasa-1 alleles from B. bovis geographical isolates originating from Argentina, USA, Brazil, Mexico and Australia showed over 98 % identity in both nucleotide and amino acid sequences. A recombinant form of GASA-1 (rGASA-1) was generated in E. coli and anti-rGASA-1 antibodies were raised in mice. Fixed and live immunofluorescence assays showed that GASA-1 is expressed in in vitro cultured B. bovis merozoites and surface-exposed. Moreover, incubation of B. bovis in vitro cultures with anti-GASA-1 antibodies partially, but significantly, reduced erythrocyte invasion, indicating that this protein bears neutralization-sensitive antibody epitopes. Splenocytes of rGASA-1-inoculated mice showed a specific proliferative response when exposed to the recombinant protein, indicating that GASA-1 bears T-cell epitopes. Finally, sera from a group of B. bovis-infected cattle reacted with the recombinant protein, demonstrating that GASA-1 is expressed during natural infection of bovines with B. bovis, and suggesting that it is immunodominant. The high degree of conservation among B. bovis isolates and the presence of syntenic genes in other Babesia species suggest a relevant role of GASA-1 and GASA-1-like proteins for parasite survival, especially considering that, due to their surface location, they are exposed to the selection pressure of the host immune system. The highlighted features of GASA-1 make it an interesting candidate for the development of vaccines against bovine babesiosis.